Pembuatan Mikroemulsi Dari Minyak Buah Merah - Jufri, Mahdi; Djajadisastra, Joshita; Maya, Ledy (Majalah Ilmu Kefarmasian, 2009)
Red fruit oil (Pandanus conoideus) is a natural product typicaly from Papua used as a medication for some disease, as a food supplement, and for beauty skin care. But this advantages are not supported by an appropriate dosage form. Oils are difficult to dissolve in GIT and difficult to penetrate the human skin, slower the absorption then. Microemulsion is a dispersion system which can help to solve the problems by enhanc-ing the oil solubility in GIT and the oil penetration through the skin. The objective of this study is to formulate a clear and stabile microemulsion. Microemulsion will be physically evaluated for 2 months. The material composition is 5% glycerin and 15% sorbitol as the cosolvent, and 20% , 30%, and 40% tween -20 as the surfactants. The result showed that formula of 40% tween-20 gave a good microemulsion which is physically stable as long as 2 months stored at room temperature.